MEDIA INFORMASI SEBAGAI BENTUK STRATEGI KOMUNIKASI PEMASARAN PADA INSTAGRAM APPLE_BTH DALAM MENARIK MINAT PEMBELI - Nidilah, Wijuli; Purwanti, Angel (LPPM Universitas Putera Batam, 2021)
Internet can be interpreted as a vast, large and worldwide computer network, which connects computer users from one place to another online. One of the online media that interests the public now is Instagram. In the economic world, Instagram can be considered as a promotional tool for business people. The purpose of this research is to know the marketing communication strategies of mobile products in attracting buyers' interest in social media like Instagram. The type of research used in this study is descriptive qualitative. The sample technique used in this research is using purposive sampling technique. Data collection techniques were carried out by means of observation, in-depth interviews, and literature study from various sources of research material. The results of this study indicate that the marketing communication strategy of mobile products in attracting buyers who are marketed by @Apple_bth uses advertising, sales promotion, personal sales, direct marketing, interactive marketing, public relations and event marketing. Mobile phone sales have risen sharply through online social media on Instagram.